Model-based dynamic estimation of water environmental capacity using grid-level simulation and functional zoning: a case study of the Ganjiang River estuary - Lu, Jiangang; Fu, Yanmei; Zhang, Liwei; Huang, Weiqi (Frontiers in Environmental Science, 2025)
To assess the water environmental capacity of the Ganjiang River estuary, this study delineated the region into six sub-areas based on designated water functional zones and established 14,600 computational grids. A field-based pollution source survey and cross-sectional water quality monitoring were conducted to characterize pollutant load distribution. A two-dimensional hydrodynamic–water quality coupled model was developed to simulate the transport and transformation of permanganate index (CODMn), ammonia nitrogen (NH3-N), and total phosphorus (TP) under 2020 hydrological conditions. Based on simulation outputs, a dynamic estimation method was proposed by integrating grid-scale pollutant concentrations, region-specific water exchange periods, and functional zone water quality standards. Results showed clear seasonal variation, with peak capacities in June–July (e.g., 4307.50 t/day for CODMn, 858.75 t/day for NH3-N, and 149.00 t/day for TP) and minima in December. Sensitivity analysis indicated that pollutant load was the dominant factor, while dispersion and degradation coefficients had weaker effects. Monte Carlo–based uncertainty analysis confirmed model robustness, with coefficients of variation <0.15 and 95% confidence intervals consistent with observations. Comparison with conventional static methods revealed that static estimates were only 80%–85% of dynamic values, underestimating capacity during high-flow periods and overestimating it in low-flow months. By explicitly considering pollutant input, degradation, and hydrodynamic transport, the proposed approach yields capacity estimates that reflect realistic residual assimilative potential, i.e., the remaining pollutant-bearing capacity after accounting for existing loads. This framework offers a practical tool for total load control, differentiated permitting, and adaptive water quality management in multi-functional estuarine systems.